Coupled cycle with Kalina cycle system and vapor absorption refrigeration. (December 2014) - Shankar, R; Srinivas, T
A combined power and cooling cycle system known as cooling cogeneration cycle has been developed by coupling a Kalina cycle system (KCS) with a single effect vapor absorption refrigeration (VAR) system using ammonia–water mixture as working fluid. In the proposed system, a flow control has been provided to choose the degree of power or cooling according to the demand. The total system is designed at equal parts of power and cooling (50% power and 50% cooling). The working fluid mass flow rate has been controlled from −20% to 20% from the equal outputs. The coupling of Kalina cycle system and vapor absorption refrigeration avoids the repetitive use of common equipment and, therefore, results in a compact size compared to conventional integration. The effects of power cycle mass split ratio, separator vapor fraction, turbine concentration, evaporator temperature, and circulating water inlet temperature have been studied on performance characteristics to maximize the energy utilization factor. An optimum separator vapor fraction has been found from 45% to 50%. A higher turbine concentration and evaporator exit temperature is recommended for favorable results. An equal working fluid share (50:50) to power and cooling results in a net power and cooling of respectively 22.5 kW and 200 kW. The cycle energy utilization factor and plant energy utilization factor are 0.23 and 0.10, respectively.